Sedimentologische und pedologische Untersuchungen zur Landschaftsgenese in der Bucht von Wissant (Pas de Calais) - Siebertz, Helmut; Siegburg, Werner (ERDKUNDE, 1991)
In the bay of Wissant various Holocene (and Pleistocene?) sediments are exposed on a c1iff wall (height: up to 15 m) in the northern part of Wissant. They reveal a differentiated landscape development in this area. The subjacent stratum, which consists of Pre-Subboreal colluvial and solifluction deposits, indicates intensive processes of redeposition. Above this stratum a fossil loamy humic horizon (W 1, Fig. 3) was found, the age of which could be determined by means of radiocarbon dating (2760 :t 30 a BP = Subboreal-Subatlanticum). It forms a significant stratigraphic break between the subjacent and the overlying strata and thus reveals a remarkable change of the paleogeographic conditions (formation of soils), which partly coincided with the formation of peat deposits in the 'petite plaine maritime' of Wissant (Calais IV - Dunkirk 0 by HAGEMAN 1969). A similar horizon can be found in numerous profiles of the French, Belgian and Dutch coast. It provides a chronostratigraphic mark within the Holocene sediments of this region. The upper strata consists of partly redeposited eolian sands which indicate another phase of landscape development. The 14C dating of a fossil soil horizon, which was formed within the eolian deposits, makes it possible to identify an older and a younger dune generation. The stratigraphic interchanging of eolian sands (dune sand, drift sand) and fossil soils give evidence of successive phases of dune or cover sand formation and stabilization.